แนวทางเสริมสร้างแรงจูงใจในการปฏิบัติงานของครู สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาศรีสะเกษ ยโสธร - เทพมณี, เกษกมล; จุลสุวรรณ์, สุวัฒน์ (วารสารพุทธปรัชญาวิวัฒน์, 2025)
การวิจัยนี้มีวัตถุประสงค์ 1) เพื่อศึกษาสภาพปัจจุบัน สภาพที่พึงประสงค์และความต้องการจำเป็นในการเสริมสร้างแรงจูงใจในการปฏิบัติงานของครู สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาศรีสะเกษ ยโสธร 2) เพื่อพัฒนาแนวทางในการเสริมสร้างแรงจูงใจในการปฏิบัติงานของครู สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาศรีสะเกษ ยโสธร การวิจัยในครั้งนี้ดำเนินการวิจัยแบ่งออกเป็น 2 ระยะ คือ ระยะที่ 1 ศึกษาสภาพปัจจุบัน สภาพที่พึงประสงค์ และความต้องการจำเป็นในการเสริมสร้างแรงจูงใจในการปฏิบัติงานของครู สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาศรีสะเกษ ยโสธร กลุ่มตัวอย่างที่ใช้ในการวิจัยเก็บรวบรวมข้อมูล ได้แก่ ครูผู้สอน จำนวน 355 คน เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูล คือ แบบสอบถาม ชนิดมาตราส่วนประมาณค่า 5 ระดับ ระยะที่ 2 ศึกษาแนวทางในการเสริมสร้างแรงจูงใจในการปฏิบัติงานของครู สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาศรีสะเกษ ยโสธร โดยผู้ทรงคุณวุฒิจำนวน 5 คน ได้มาโดยการเลือกแบบเจาะจง เครื่องมือที่ใช้ในการวิจัย คือ แบบประเมินความเหมาะสมของการพัฒนาแนวทางเสริมสร้างแรงจูงใจในการปฏิบัติงานของครู สถิติในการวิเคราะห์ข้อมูล ได้แก่ ความถี่ ร้อยละ ค่าเฉลี่ย ส่วนเบี่ยงเบน มาตรฐาน และค่าดัชนีความต้องการจำเป็น ผลการวิจัยพบว่า 1) ครูในสังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาศรีสะเกษ ยโสธร มีความคิดเห็นต่อสภาพปัจจุบันของแรงจูงใจในการปฏิบัติงานของครู โดยรวมอยู่ในระดับน้อย และสภาพที่พึงประสงค์ของแรงจูงใจในการปฏิบัติงานของครู โดยรวมอยู่ในระดับมากที่สุด และความต้องการจำเป็นในการเสริมสร้างแรงจูงใจในการปฏิบัติงานของครู เรียงลำดับจากมากไปหาน้อย ได้แก่ 1) ผลตอบแทนที่เกิดจากการปฏิบัติงาน 2) สภาพแวดล้อมในการทำงาน 3) การได้รับความสำเร็จในการทำงาน 4) การได้รับการยอมรับนับถือ 5) ลักษณะของงานที่ปฏิบัติ 6) ความสัมพันธ์ที่ดีภายในองค์กร และ 7) ความมั่นคงและปลอดภัยในการทำงาน และ 2) การพัฒนาแนวทางในการเสริมสร้างแรงจูงใจในการปฏิบัติงานของครู สังกัดสำนักงานเขตพื้นที่การศึกษามัธยมศึกษาศรีสะเกษ ยโสธร ประกอบด้วย 7 ด้าน ได้แก่ 1) การได้รับความสำเร็จในการทำงาน 2) การได้รับการยอมรับนับถือ 3) ความสัมพันธ์ที่ดีภายในองค์กร 4) ผลตอบแทนที่เกิดจากการปฏิบัติงาน 5) สภาพแวดล้อมในการทำงาน 6) ลักษณะของงานที่ปฏิบัติ และ 7) ความมั่นคงและปลอดภัยในการทำงาน ทั้ง 7 ด้าน มีการพัฒนาแนวทางในการเสริมสร้างแรงจูงใจในการปฏิบัติงานของครู รวมทั้งสิ้น 54 แนวทาง โดยรวมมีความเหมาะสมอยู่ในระดับมากที่สุด The purposes of this study were: 1) to study the current condition Desirable conditions and needs to enhance teachers' motivation to work. Under the Secondary Educational Service Area Office Si Sa Ket Yasothon. 2) To develop guidelines for enhancing teachers' work motivation. Under the Secondary Educational Service Area Office Si Sa Ket Yasothon, this research the research is divided into 2 phases: Phase 1 is a study of the current condition. Desired condition and necessary needs for Strengthen teachers' motivation in their work. Under the jurisdiction of the Secondary Educational Service Area Office Si Sa Ket Yasothon, the sample group used in the data collection research included 355 teachers. The instrument used for data collection was a questionnaire, 5-level rating scale, Phase 2, study of guidelines. To enhance teachers' motivation in their work. Under the jurisdiction of the Secondary Educational Service Area Office Si Sa Ket Yasothon, by 5 qualified experts obtained through purposive selection. The tool used in the research was a form to evaluate the appropriateness of developing guidelines for enhancing teachers' work motivation. Statistics for data analysis include frequency, percentage, mean, standard deviation. And the index of essential needs The result of the research revealed that: 1) Teachers under the Secondary Educational Service Area Office Si Sa Ket Yasothon have opinions on the current state of motivation for teachers' work. Overall, it is at a low level. And the desired conditions of motivation for teachers' work performance. Overall, it is at the highest level. As for the need to enhance teachers' motivation in their work, arranged from most to least: 1) the rewards resulting from the work, 2) the dimension of the work environment, 3) the aspect of achieving success at work, 4) the aspect of being accepted and respected, 5) the nature of the work performed, 6) the good relationships within the organization, and 7) the aspect of stability and occupational safety and 2) Developing guidelines to enhance teachers' motivation in their work. Under the jurisdiction of the Secondary Educational Service Area Office Si Sa Ket Yasothon, it consists of 7 aspects: 1) receiving success in work, 2) being respected, 3) good relationships within the organization, 4) Rewards from performance, 5) Work Environment, 6) the nature of work performed, and 7) Stability and Occupational Safety in all 7 areas. There were 54 guidelines developed to enhance teachers' work motivation. Overall, they were at the highest level of appropriateness.